1986
DOI: 10.1002/aic.690320814
|View full text |Cite
|
Sign up to set email alerts
|

Tracer diffusion in dense ethanol: A generalized correlation for nonpolar and hydrogen‐bonded solvents

Abstract: Tracer diffusion coefficients were measured for benzene, toluene, mesitylene, naphthalene, and phenanthrene in dense ethanol at 0.56 5 TR 5 1.07 and pR 2 1.44. The results were used to examine the temperature dependence of the degree of association between ethanol molecules across the entire range of temperature. The hard-sphere tracer diffusion equation and the Stokes-Einstein equation were used to develop two engineering correlations. The former approach was found to be adequate for solvents of relatively co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

1988
1988
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(27 citation statements)
references
References 14 publications
3
24
0
Order By: Relevance
“…The above experimental results are in agreement with the MCT study of Bhattacharyya and Bagchi,25(b) which found that the effect of solute mass on diffusion is generally quite weak; in particular, the solute-mass dependence can normally be considered as negligibly small when changes of solute mass are small within a factor of 2 or so. It should be pointed out that it 51,53,54 have reported tracer diffusivities of nonassociated aromatic solutes in cyclohexane, ethanol, and n-hexane at temperatures above 298.2 K. We have carried out linear regressions for their data at temperatures below the normal boiling point of solvent (but excluding those data at higher temperatures which were measured at different pressures above 1 atm). All data, except one of Dymond's 14 In view of the correlation coefficients and the average % deviations for the 13 sets of linear regressions in Table II, it is clear that Eq.…”
Section: A Solute Dependencementioning
confidence: 99%
“…The above experimental results are in agreement with the MCT study of Bhattacharyya and Bagchi,25(b) which found that the effect of solute mass on diffusion is generally quite weak; in particular, the solute-mass dependence can normally be considered as negligibly small when changes of solute mass are small within a factor of 2 or so. It should be pointed out that it 51,53,54 have reported tracer diffusivities of nonassociated aromatic solutes in cyclohexane, ethanol, and n-hexane at temperatures above 298.2 K. We have carried out linear regressions for their data at temperatures below the normal boiling point of solvent (but excluding those data at higher temperatures which were measured at different pressures above 1 atm). All data, except one of Dymond's 14 In view of the correlation coefficients and the average % deviations for the 13 sets of linear regressions in Table II, it is clear that Eq.…”
Section: A Solute Dependencementioning
confidence: 99%
“…Since the supercritical conditions from Pottinger were similar to the conditions used by Li and Kiran for methylamine delignification of wood (Li, 1989), mean specific volume values from Pottinger were used to estimate the critical molar volume for the complex. The methylamine viscosity and the complex critical molar volume were used with the correlation of Sun and Chen (Sun, 1986) to estimate the complex molecular diffusivity. Chang's method (Chang, 1982) was used to estimate the effective diffusivity based on molecular diffusivity.…”
Section: Methylamine-lignin Complex Propertiesmentioning
confidence: 99%
“…Diffusion coefficients in propane were simply interpreted [43] in terms of the StokesEinstein coefficients [44]. In a series of papers, Sun and Chen measured diffusion coefficients of several aromatic and aliphatic hydrocarbons in near-or supercritical cyclohexane [45], 2,3-dimethylbutane [46], n-hexane 1471, ethanol [48], and methanol and 2propanol [49]. The results were represented by a rough-hard-sphere model, and the diffusivity data in the hydrogen-bonded fluids were used to obtain information on the degree of molecular association of the respective fluid.…”
Section: Diflfztsion Measurements Taylor Dispersion Technique This Tmentioning
confidence: 99%